An investigation of soilborne fungi associated with roots and crowns of nursery grapevines - Van Coller, Gerhardus J. (Gerhardus Johannes) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--University of Stellenbosch, 2004.